Implementasi Program Penanggulangan Stunting di Dinas Kesehatan Pengendalian Penduduk, dan Keluarga Berencana Kota Tanjungpinang - Farida Hani Sri Wahyuni; Rumzi Samin; Rudi Subiyakto; Fitri Kurnianingsih (Lembaga Pengembangan Kinerja Dosen, 2023)
Stunting is a lack of nutritional intake with a long duration, starting from pregnancy to 24 months. The prevalence of stunted children recorded at the Tanjungpinang City Health, Population Control, and Family Planning Office increased by 1.3% in 2020 to 3.49% in 2021 and 3.91% in 2022. Based on these data, it can be seen that there has been an increase in stunting cases in Tanjungpinang City. The problem that will be the focus of discussion in this study is how to implement stunting prevention programs in the Tanjungpinang City Health, Population Control and Family Planning Office. This study aims to analyze the implementation of stunting prevention programs in the Tanjungpinang City Health, Population Control and Family Planning Office.The research approach used in this study is explained using a qualitative approach. The theory used by researchers in implementation uses Soren C. Winter's theory which includes indicators: the behavior of relationships between organizations, the behavior of lower-level implementors (apparatus / bureaucrats) and the behavior of target groups. The implementation of the stunting alleviation program at the Tanjungpinang City Health, Population Control and Family Planning Office has been going well, but it is still not optimal. This is because there are still people who do not know about stunting, socialization carried out by puskesmas officers and posyandu cadres has not been thoroughly carried out. However, the response from the community itself is very good or positive, this is because puskesmas officers continue to provide assistance and check regularly. The commitment made by the health Office in collaboration with the Ministry of Religious Affairs made an MOU so that these brides-to-be get IEC (Educational Information Communication) and with the formation of the Stunting Reduction Acceleration Team at the Tanjungpinang City level, this is nothing but an effort to reduce stunting rates in Tanjungpinang City.